Kata-kata Serapan dalam Alquran Perspektif Ulama Tafsir - Fajriyani Arsya (Tamaddun, 2019)
One of the issues debated by Arab linguists and interpreters of the Quran is whether all the words in the Koran come from native Arabic, or are there uptake words from foreign languages used in the Koran. The analysis of linguists states that the absorption words in various languages can arise due to geographical location, trade relations, immigration, politics, culture, economy, industry, and others. In the context of absorption words in the Koran the scholars are divided into three opinions, namely the group of scholars who reject the absorption of words in the Koran; Second, groups who believe that there are absorption words in the Koran; and third, which takes a middle ground with a view that the word uptake in the Koran has its specificities.